1976
DOI: 10.1172/jci108396
|View full text |Cite
|
Sign up to set email alerts
|

Permselectivity of the glomerular capillary wall. Studies of experimental glomerulonephritis in the rat using dextran sulfate.

Abstract: A B S T R A C T To determine whether the increased filtration of serum proteins after glomerular injury is the consequence of altered electrostatic properties of the glomerular capillary wall, we measured fractional clearances of the anionic polymer, dextran sulfate, in nine Munich-Wistar rats in the early autologous phase of nephrotoxic serum nephritis (NSN). In agreement with previous studies from this laboratory, whole kidney and single nephron glomerular filtration rates were normal in NSN rats despite his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(52 citation statements)
references
References 26 publications
5
47
0
Order By: Relevance
“…With the use of dextran polymers of broad size distribution and varying charge density, it has been shown that rodent nephrotoxic seru'm nephritis is accompanied by reduction of fixed negative charges on the diseased glomerular capillary wall leading to less restriction of circulating polyanions (10,13,37). Our analysis of excreted urinary proteins provides indirect evidence that this is also true of patients with proliferative glomerulonephritis.…”
Section: Discussionmentioning
confidence: 70%
“…With the use of dextran polymers of broad size distribution and varying charge density, it has been shown that rodent nephrotoxic seru'm nephritis is accompanied by reduction of fixed negative charges on the diseased glomerular capillary wall leading to less restriction of circulating polyanions (10,13,37). Our analysis of excreted urinary proteins provides indirect evidence that this is also true of patients with proliferative glomerulonephritis.…”
Section: Discussionmentioning
confidence: 70%
“…Having established in the above studies that inulin appears in Bowman's space in the same concentration as in plasma water in NSN rats and that fractional urinary dextran clearances are the same as fractional dextran clearances measured for single accessible glomeruli in the same kidney (i.e., dextrans are neither secreted nor reabsorbed), justification is provided for relying on urinary clearances to assess the permselectivity 2Throughout this and the accompanying paper (14), concentrations of all solutes in plasma are expressed in terms of mass per unit volume of plasma water.…”
Section: Animal Studiesmentioning
confidence: 99%
“…As discussed in detail in the companion report (14), this apparent discrepancy may be explained by disease-induced alterations of the fixed charge residing on the structural barrier to transport, the effect of which is to increase the permeability of the glomerular capillary wall to polyanionic, but not neutral, macromolecules.…”
mentioning
confidence: 99%
“…This distribution of early epimembranous complex deposits corresponds to the localization of polyanionic glomerular sialoprotein on epithelial cells and in filtration slits (17)(18)(19). Recent physiologic and ultrastructural tracer studies have suggested a role for this negatively charged material in regulating the permeability of the glomerular capillary wall to circulating macromolecules in both normal and disease states (20)(21)(22)(23)(24). However, the effect of alterations in intrinsic properties of the glomerulus on the localization of immune complexes has not been previously investigated.…”
mentioning
confidence: 99%